Metal Leachability, Mechanical Properties And Surface Characterisation Of Ti6al4v Dental Implants - Sukumaran, Binsu (2021)
Implanted prosthetic devices have become an integral modality in restorative dentistry. Biological risk associated with ionic particles released from metallic implants are critical and very much sought after. This study is divided into in vitro and in vivo. The main objective of the study was to evaluate metal leaching from dental implants Ti6Al4V. Specifically, the in vitro part aimed to analyse metal leaching from dental implants in simulated body fluid (SBF) at different pH (3.0, 5.5, 6.5, 7.3,7.5 and 7.8) using inductively coupled plasma mass spectrometry (ICP-MS) with electrochemical corrosion and mechanical properties evaluation.